Unpacking the Biographical Antecedents of the Emergence of Social Enterprises: A Narrative Perspective - Chandra, Yanto; Shang, Liang (Voluntas (Manchester, England), 2017)
Despite the burgeoning research on social enterprise (SE), there is a dearth of research that investigates the biographical factors that influence the emergence of SEs in the form of hybrid organizations on a large scale. Drawing on the emerging narrative perspective of SE, we examine the biographical narratives of 317 self-identified social entrepreneurs who were selected as fellows by two of the world's largest SE support organizations: Ashoka and the Schwab Foundation. We employ Gioia's methodology and principal component analysis to derive and subsequently classify the biographical antecedents of SE emergence. This study makes a novel contribution to the SE-as-hybrid-organization literature by revealing eight biographical antecedents of SE emergence, four of which can be categorized into social skills, and four others can be categorized into economic skills, which constitute SE's social position. We also develop a typology of SE based on different combinations of individuals' social skills and social position. Finally, we discuss the implications of this study for the SE-as-hybrid-organization literature, highlight its limitations, and present possible avenues for future research. Malgré les recherches de plus en plus nombreuses sur les entreprises sociales (ES), trop peu enquêtent sur les facteurs biographiques qui influencent l'émergence des ES en tant qu'organismes hybrides de grande échelle. En s'inspirant du point de vue narratif émergent des ES, nous étudions les faits biographiques exposés par 317 entrepreneurs sociaux déclarés, qui ont été faits membres de deux des plus grandes organisations de soutien des ES au monde : Ashoka et la Fondation Schwab. Nous employons la méthode de Gioia et une analyse des principaux éléments concernés pour dériver et subséquemment classer les antécédents biographiques de l'émergence des ES. La présente étude fait une contribution inédite à la documentation sur les organismes d'entreprise sociale hybrides en révélant huit antécédents biographiques de l'émergence des ES, dont quatre pouvant être classés sous la rubrique compétences sociales et quatre sous compétences économiques, représentant ainsi le positionnement social des ES. Nous avons aussi élaboré une typologie des ES en fonction de diverses combinaisons de compétences et positions sociales individuelles. Nous discutons enfin des implications de cette étude dans le contexte de la documentation sur les organismes ES hybrides, en soulignant ses limites et présentant de possibles voies de recherche futures. Trotz zunehmender Forschungen zu Sozialunternehmen mangelt es an Studien, die die biographischen Faktoren in großem Umfang untersuchen, welche die Entstehung von Sozialunternehmen in Form von Hybridorganisationen beeinflussen. Wir stützen uns auf die neu hervortretende Erzählperspektive von Sozialunternehmen und untersuchen die biographischen Schilderungen von 317 selbstidentifizierten Sozialunternehmern, die von zwei der weltweit größten Organisationen zur Unterstützung von Sozialunternehmen - Ashoka und Schwab Foundation - als Partner gewählt wurden. Wir wenden die Gioia-Methode und Hauptkomponentenanalyse an, um die biographischen Antezedenzien für die Entstehung von Sozialunternehmen abzuleiten und anschließend zu klassifizieren. Diese Studie leistet einen ganz neuen Beitrag zur Literatur zum Thema Sozialunternehmen als Hybridorganisationen, indem sie acht biographische Antezedenzien für die Entstehung von Sozialunternehmen aufdeckt, von denen vier als soziale Fertigkeiten und die anderen vier als ökonomische Fertigkeiten klassifiziert werden können, die die soziale Stellung eines Sozialunternehmens begründen. Darüber hinaus entwickeln wir eine Typologie für Sozialunternehmen beruhend auf verschiedenen Kombinationen aus den sozialen Fertigkeiten einzelner Personen und der sozialen Stellung. Abschließend diskutieren wir die Implikationen dieser Studie für die Literatur zum Thema Sozialunternehmen als Hybridorganisationen, heben die Beschränkungen hervor und präsentieren mögliche zukünftige Forschungsrichtungen. A pesar de la floreciente investigación sobre la empresa social (SE, por sus siglas en inglés), existe una escasez de investigación que estudie los factores biogrâficos que influyen en el surgimiento de SE en la forma de organizaciones hibridas a gran escala. Recurriendo a la perspectiva narrativa emergente de la SE, examinamos las narrati vas biogrâficas de 317 emprendedores sociales que se identificaron corno tales y que fueron seleccionados corno miembros por dos de las organizaciones de apoyo a las SE más grandes del mundo: Ashoka y la Schwab Foundation. Empleamos la metodología de Gioia y el análisis de componentes principales para derivar y clasificar posteriormente los antecedentes biográficos del surgimiento de la SE. El presente estudio realiza una novedosa contribución al material publicado sobre la SE corno organización hibrida revelando ocho antecedentes biográficos del surgimiento de la SE, cuatro de los cuales pueden ser clasificados en habilidades sociales, y otros cuatro pueden ser clasificados en habilidades económicas, que constituyen la posición social de la SE. También desarrollamos una tipologia de SE basada en diferentes combinaciones de habilidades sociales y posición social de los individuos. Finalmente, tratamos las implicaciones del presente estudio para el material publicado sobre la SE corno organizacion hibrida, destacamos sus limitaciones y presentamos posibles vias para investigaciones futuras.